Control of Electric Car Wheel Rotation Speed Using an Accelerometer Sensor (MPU-6050) - Faalah, Fadjar Nur; Hanna, Ahmad Zyusrotul; Ma'arif, Alfian (Signal and Image Processing Letters, 2021)
In the modern era, the implementation of electrification technology is one of the efforts that needs to be applied to create fuel-efficient and environmentally friendly vehicles. This technology encompasses various types, ranging from hybrid to full electric vehicles. There are four types of electric vehicle drivetrains and power sources used, namely: Battery Electric Vehicle (BEV), Hybrid Electric Vehicle (HEV), Plug-in Hybrid Electric Vehicle (PHEV), and Fuel Cell Electric Vehicle (FCEV). The prototype system of an electric car aims to create an Electrical Control Unit (ECU) with a feature that enhances acceleration in a multifunctional electric car, which can be used in both conventional and unconventional vehicles, such as Formula-E racing cars. The participation in creating an electric car prototype is used for testing the speed control of electric cars using an accelerometer sensor (MPU-6050) placed on the steering wheel, similar to electrification technology. The drivetrain technology aims to improve acceleration (the change in speed within a specific time unit) in electric cars. The components used in creating the electric car prototype include the main components such as the Arduino Uno R3 microcontroller, MPU-6050 sensor, and potentiometer.